Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s12142-011-0202-2
|View full text |Cite
|
Sign up to set email alerts
|

‘The Cooling of Hearts’: Community Truth-Telling in Northern Uganda

Abstract: Recent national and international debates on truth and reconciliation in Uganda have emphasized the importance of incorporating local-level mechanisms into a national transitional justice strategy. The Juba Peace Talks represented an opportunity to develop and articulate sufficient and just alternatives and compleHum Rights Rev (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The Survey for War Affected Youth (SWAY) found that only 22% of females had accessed a traditional cleansing ceremony [ 26 ], however the SWAY study was conducted in 2005 and it is possible that the current findings reflect the temporal trends in DDR programming over the evolution of the conflict beyond 2005 and perhaps increased effort to include women and girls in DDR programming. An important barrier for traditional ceremonies are the associated costs, particularly for orphans who lack basic resources [ 19 , 32 ]. It is encouraging to see that, despite the large proportion of female single or double orphans (>85%) in this study, many still had access to traditional ceremonies.…”
Section: Discussionmentioning
confidence: 99%
“…The Survey for War Affected Youth (SWAY) found that only 22% of females had accessed a traditional cleansing ceremony [ 26 ], however the SWAY study was conducted in 2005 and it is possible that the current findings reflect the temporal trends in DDR programming over the evolution of the conflict beyond 2005 and perhaps increased effort to include women and girls in DDR programming. An important barrier for traditional ceremonies are the associated costs, particularly for orphans who lack basic resources [ 19 , 32 ]. It is encouraging to see that, despite the large proportion of female single or double orphans (>85%) in this study, many still had access to traditional ceremonies.…”
Section: Discussionmentioning
confidence: 99%
“…Mato Oput broadly translates as "drinking (mato) of the bitter root (oput). " As summarized by Anyeko et al (2012), mato oput is a voluntary process that begins with negotiations and mediation between the families involved to develop trust and establish the truth. Thereafter negotiations are held about the amount of compensation to be paid.…”
Section: Revisiting Assumptions Ab Out Gender C Onflict Violence mentioning
confidence: 99%
“…In its modern form, the ritual can also be seen as the outcome of a voluntary restorative traditional justice process involving a confession of truth that will eventually lead to compensation (Angucia, 2010; Baines, 2007; cf. Anyeko et al., 2012).…”
Section: A Ritual Repositorymentioning
confidence: 99%
“…In social worlds dominated by the belief that evil lurks in human relationships, children may also be implicated in the diagnostic and curative processes aimed at Reis redressing social wrongs. In Northern Uganda, Acholi children complain of cen, spirits of people who died during the war and who haunt the living until they are appeased Akello, Reis, & Richters, 2010;Akello, Richters, & Reis, 2009;Angucia, 2010;Anyeko et al, 2012;cf. Liu Institute, Gulu District NGO Forum, and Ker Kwaro Acholi, 2005;Neuner et al, 2012).…”
Section: Children Spirits and Witchesmentioning
confidence: 99%